2017
DOI: 10.3389/fnhum.2017.00504
|View full text |Cite
|
Sign up to set email alerts
|

An Emotion-Enriched Context Influences the Effect of Action Observation on Cortical Excitability

Abstract: Observing other people in action activates the “mirror neuron system” that serves for action comprehension and prediction. Recent evidence suggests that this function requires a high level codification triggered not only by components of motor behavior, but also by the environment where the action is embedded. An overlooked component of action perceiving is the one related to the emotional information provided by the context where the observed action takes place. Indeed, whether valence and arousal associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Importantly, we demonstrated that this cue-dependent facilitation is grip specific (de Beukelaar et al 2016) and persists even if the movement kinematics are occluded from view. Neurophysiological studies in humans and nonhuman primates support this idea by showing that mirror activity is influenced by nonkinematic triggers (Avanzino et al 2015;Lagravinese et al 2017;Lehner et al 2017;Maranesi et al 2014;Saucedo Marquez et al 2011) and is still present when well-known actions are occluded from view (Umiltà et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, we demonstrated that this cue-dependent facilitation is grip specific (de Beukelaar et al 2016) and persists even if the movement kinematics are occluded from view. Neurophysiological studies in humans and nonhuman primates support this idea by showing that mirror activity is influenced by nonkinematic triggers (Avanzino et al 2015;Lagravinese et al 2017;Lehner et al 2017;Maranesi et al 2014;Saucedo Marquez et al 2011) and is still present when well-known actions are occluded from view (Umiltà et al 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Prior evidence shows an association between CSE and emotion with negative emotional stimuli mediating higher CSE, such as threatening 109 , fearful 110 , and disgusting 111 112 stimuli. However, the type of negative emotion is important as there is an inverse association between depressive mood and CSE 113 with further evidence showing no effect of sadness on CSE 114 . Moreover, CSE is reduced during the perception of painful stimuli, suggesting a suppression of bodily recruitment due to empathetic cognitive processes associated with distancing oneself from such pain 115 .…”
Section: Embodiment and Empathymentioning
confidence: 99%
“…In a previous research, we looked at how watching a movement carried out in a negative emotional setting affected motor resonance [ 4 ]. We concentrated on negative emotions (sadness and disgust) at various levels of arousal [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous research, we looked at how watching a movement carried out in a negative emotional setting affected motor resonance [ 4 ]. We concentrated on negative emotions (sadness and disgust) at various levels of arousal [ 4 ]. Our findings suggested that the emotional context in which a movement occurs increases motor resonance in a combination of negative valence/high arousal contexts, as evidenced by greater motor resonance (i.e., larger amplitude of MEPs) during the observation of the movement in the context eliciting disgust compared with the others [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation